2006
DOI: 10.1021/es051682z
|View full text |Cite
|
Sign up to set email alerts
|

Perchlorate Reduction by Autotrophic Bacteria in the Presence of Zero-Valent Iron

Abstract: A series of batch experiments were performed to study the combination of zero-valent iron (ZVI) with perchlorate-reducing microorganisms (PRMs) to remove perchlorate from groundwater. In this method, H2 produced during the process of iron corrosion by water is used by PRMs as an electron donor to reduce perchlorate to chloride. Perchlorate degradation rates followed Monod kinetics, with a normalized maximum utilization rate (rmax) of 9200 microg g(-1) (dry wt) h(-1) and a half-velocity constant (Ks) of 8900 mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
46
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(55 citation statements)
references
References 20 publications
6
46
0
3
Order By: Relevance
“…The inhibitory effect of zero-valent iron on perchlorate was attributed to the increase in pH and encapsulation of bacteria by iron precipitates. High concentrations of bicarbonate (1260 mg/L) and phosphate (430 mg/L) in the culture media resulted in the formation of vivianite, Fe 3 (PO 4 ) 2 , and siderite, FeCO 3 , the major iron precipitates identified on Shrout et al (2005) research, but Yu et al (2006) claim they are not likely to occur in typical groundwater conditions. In contrast, Yu et al (2006) showed that zero-valent iron was capable of serving as electron donor for perchlorate reduction by providing hydrogen to a hydrogen utilizing autotroph (Dechloromonas sp.…”
Section: Technology Development Statusmentioning
confidence: 99%
“…The inhibitory effect of zero-valent iron on perchlorate was attributed to the increase in pH and encapsulation of bacteria by iron precipitates. High concentrations of bicarbonate (1260 mg/L) and phosphate (430 mg/L) in the culture media resulted in the formation of vivianite, Fe 3 (PO 4 ) 2 , and siderite, FeCO 3 , the major iron precipitates identified on Shrout et al (2005) research, but Yu et al (2006) claim they are not likely to occur in typical groundwater conditions. In contrast, Yu et al (2006) showed that zero-valent iron was capable of serving as electron donor for perchlorate reduction by providing hydrogen to a hydrogen utilizing autotroph (Dechloromonas sp.…”
Section: Technology Development Statusmentioning
confidence: 99%
“…10,38 O processamento de águas residuais, para a produção de hidrogênio foi testado usando bactérias fermentativas em vários tipos de processos. 41,[44][45][46] Entretanto, estes processos não têm sido muito utilizados, devido à baixa recuperação de energia da matéria orgânica (1,4 -2,5 mols de hidrogênio por mol de hexose) e elevados custos operacionais. 11,46 Efluentes provenientes das indústrias de processamento de alimentos ou vindos da pecuária de animais em regime de confinamento são poluentes ambientais ideais para o bioprocessamento, pois contêm altos níveis de material orgânico facilmente degradável, cujo resultado é um saldo positivo de energia ao final do processo.…”
Section: Tratamento De Resíduos Agroindustriaisunclassified
“…41,[44][45][46] Entretanto, estes processos não têm sido muito utilizados, devido à baixa recuperação de energia da matéria orgânica (1,4 -2,5 mols de hidrogênio por mol de hexose) e elevados custos operacionais. 11,46 Efluentes provenientes das indústrias de processamento de alimentos ou vindos da pecuária de animais em regime de confinamento são poluentes ambientais ideais para o bioprocessamento, pois contêm altos níveis de material orgânico facilmente degradável, cujo resultado é um saldo positivo de energia ao final do processo. Como efluentes são fontes potenciais de energia, a recuperação desta ou a transformação destes efluentes em subprodutos úteis pode reduzir o custo do tratamento e, em alguns casos, diminuir também a nossa dependência dos combustíveis fósseis.…”
Section: Tratamento De Resíduos Agroindustriaisunclassified
“…Bu problemlerin üstesinden gelmek için reaksiyon ortamında hidrojeni oluşturabilen alternatif yaklaşımlar araştırılmıştır. Sıfır değerlikli demir (ZVI) önemli bir alternatif olarak Till vd., (1998) tarafından araştırılmış [1] ve denitrifikasyon sistemlerinde hidrojen ile ilgili problemlerin üstesinden anaerobik demir korozyonu (reaksiyon (2)) ile gelinebileceğini açıklamışlardır [18,1,16,19].…”
Section: Introductionunclassified